Analisa Pengaruh Kualitas Aplikasi Terhadap Kepuasan Pelanggan Tokopedia Menggunakan Metode PIECES Framework - Auliya Noor (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Indonesia is one of the countries whose buying and selling activities have shifted from traditional buying and selling activities to electronic ones. This is evidenced by the increasing prevalence of e-commerce applications which are directly proportional to the number of people who have downloaded them. With so many e-commerce applications out there, everyone has their own opinion when using the application. This can be seen in the number of user ratings on each e-commerce application, such as the Tokopedia application. The purpose of this study was to determine the effect of the quality management of the Tokopedia platform on customer satisfaction. The method used in this study is the PIECES Framework which includes 6 dimensions of performance, information, economics, control and security, efficiency, and service variables for the Tokopedia E-commerce Application. In this study, measurements were carried out using the PIECES Framework, resulting in an average score of 3,60 with a Likert scale. So service users are categorized as PUAS for the Tokopedia application information system service.